Phenotypes of Obesity Hypoventilation Syndrome: Characteristics and Outcomes - Masa-Jiménez, Juan F.; Ramírez-Molina, Victor R.; De Dios-Calama, Celia (Seminars in Respiratory and Critical Care Medicine, 2025)
Obesity hypoventilation syndrome (OHS) is defined by the combination of obesity (body mass index [BMI] ≥30 kg/m2), sleep-disordered breathing, and daytime hypercapnia (arterial carbon dioxide tension [PaCO2] ≥45 mm Hg at sea level) during wakefulness occurring in the absence of an alternative neuromuscular, mechanical, or metabolic explanation for hypoventilation. Patients with OHS can be classified by phenotypes depending on whether or not they have obstructive respiratory events: hypoventilation and no or not significant obstructive sleep apnea (OSA) and hypoventilation and significant OSA; we also add a third phenotype, which is the hospitalized patient with acute-on-chronic respiratory failure. We describe the mid- and long-term outcomes with and without positive airway pressure (PAP) by these three phenotypes.
Keywords: obesity hypoventilation syndrome; apnea; positive airway pressure; CPAP; non-invasive ventilation